2014
DOI: 10.1080/0735648x.2014.929975
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of the effect of correctional officers’ bases of power on their fear and risk of victimization

Abstract: Despite research on disorder in prison, knowledge is limited regarding keeping order within the correctional environment. A sector of this research delves into how the uses of correctional officer power influence inmate compliance and support the goals of the institution, but no research has examined how officers rely on different power bases because of their own fear and risk of victimization; the current study preliminarily explores this issue. This study used the results of a self-administered survey of 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
1
33
0
1
Order By: Relevance
“…The latter suggests that once workplace factors are taken into account, personal characteristics do not play as great a role in predicting perceived risk of danger on the job. The present study revealed higher perceptions of danger among nonWhites, which is consistent with prior research examining perception of fear of victimization (see Gordon & Baker, 2015;Gordon et al, 2013;Stichman & Gordon, 2015;Taxman & Gordon, 2009). This held only for the entire sample of correctional staff; the race variable was not significant for the subset of custody officers or among non-custody staff, but it did come close to statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The latter suggests that once workplace factors are taken into account, personal characteristics do not play as great a role in predicting perceived risk of danger on the job. The present study revealed higher perceptions of danger among nonWhites, which is consistent with prior research examining perception of fear of victimization (see Gordon & Baker, 2015;Gordon et al, 2013;Stichman & Gordon, 2015;Taxman & Gordon, 2009). This held only for the entire sample of correctional staff; the race variable was not significant for the subset of custody officers or among non-custody staff, but it did come close to statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…The impact of such relationships on the daily work environment, retention of correctional staff, and the climate and culture of the institutional environment is commonly investigated (Cullen et al, 1985;Dowden & Tellier, 2004;Griffin, 2001;Lambert, Cluse-Tolar, & Hogan, 2007;Stichman & Gordon, 2015;Taxman & Gordon, 2009). Understanding the correlates of correctional staff perceptions on the dimension of workplace well-being or possible victimization by inmates is emerging in the literature (Gordon & Baker, 2015;Gordon et al, 2003;Gordon et al, 2013;Lai et al, 2012;Stichman & Gordon, 2015;Taxman & Gordon, 2009). This body of research examines perceptions of correctional officers' fear (emotional) and risk (cognitive) of primarily victimization by inmates at both the juvenile and adult levels, in the United States and overseas, and within single institutions or across multiple facilities.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Also relevant to consider, however, is how officers exercise their authority in general. How power holders exercise their power in general influences whether they maintain legitimacy and ultimately compliance (Bottoms and Tankebe, ; Stichman and Gordon, ; Wooldredge and Steiner, ). An understanding of the “dialogic nature” of the legitimacy–compliance relationship requires consideration of how power recipients perceive power holders in conjunction with how power holders behave (Bottoms and Tankebe, ).…”
Section: Prison Officers’ Exercise Of Power and Inmate Rule Breakingmentioning
confidence: 99%
“…The findings from these studies have underscored the relevance of inmate characteristics (e.g., age), features of prison environments (e.g., crowding), and management practices (e.g., use of disciplinary housing) for predicting rule breaking (Bottoms, ; Steiner, Butler, and Ellison, ). Few scholars have considered the potential influence of prison officers, and Stichman and Gordon () noted the contradiction in ignoring officer factors in related research (especially regarding inmate threats to safety, as they examined) given their vital role in managing prisoner populations. This gap in the literature is striking because prison officers are responsible for directly transmitting prison policy and penal culture to the confined (Garland, ; Lipsky, ; Vuolo and Kruttschnitt, ).…”
mentioning
confidence: 99%
“…Correctional officers' concerns about criminal victimisation have received more attention, although this body of literature is small and predominantly quantitative. Predictors of correctional facility officers' fear and perceived likelihood of victimisation include factors such as job satisfaction (which may also be an outcome of fear and perceived risk), level of workplace disorganisation, and institutional characteristics such as security level, number of inmates and whether it is a female or male facility(Gordon and Baker 2017;Gordon, Moriarty and Grant 2003;Gordon, Proulx and Grant 2013;Stichman and Gordon 2015).…”
mentioning
confidence: 99%